Antioxidative and anticancer effects of Tacca chantrieri extract enhancing cisplatin sensitivity in cholangiocarcinoma cells. - Napat Armartmuntree; Yingpinyapat Kittirat; Bundit Promraksa; Watcharin Loilome; Hasaya Dokduang; Anchalee Techasen; Pahol Sansomchai; Malinee Thanee; Thomas O'Connor; Phutthida Kongthitilerd; Sureerat Padthaisong (PLoS ONE)
Cholangiocarcinoma (CCA) poses a significant healthcare challenge due to the limited effects of chemotherapeutic drugs. Natural products have gained widespread attention in cancer research according to their promising anti-cancer effects with minimal adverse side effects. This study explored the potential of Tacca chantrieri (TC), a plant rich in bioactive compounds, as a therapeutic agent for CCA. TC, a traditional remedy in Southeast Asia, exhibits anti-inflammatory and cytotoxic properties against cancer cells. Ethanol extraction of TC's rhizome was conducted, and antioxidant activities were assessed through various assays, including total phenolic and flavonoid contents, DPPH radical scavenging, and FRAP assays. The cytotoxic effects of TC extracts on CCA cell lines (KKU-213A and KKU-213C) were evaluated using MTT assays and flow cytometry. Protein levels of Bax and Bcl-2 were determined through western blot analysis. Additionally, the study investigated whether the combined impact of TC extract and cisplatin on CCA cells enhanced cisplatin's efficacy as an anti-cancer treatment. Results indicated that ethanolic extracts from TC contained phenolic and flavonoid compounds with robust antioxidant activity. TC treatments reduce CCA cell viability, inhibiting growth and inducing apoptosis in a dose-dependent manner. The Bax/Bcl-2 ratio increases, signifying a pro-apoptotic shift. Importantly, TC extract not only decreases cell viability but also augments the inhibitory effect of cisplatin in CCA cells. These results provide valuable insights into TC's therapeutic mechanisms and its potential to synergize with conventional chemotherapeutic agents, offering a promising avenue for the development of alternative and more effective strategies for CCA treatment.